PENGARUH MARKETING MIX (7P) TERHADAP LOYALITAS PASIEN DI RUMAH SAKIT: TINJAUAN SISTEMATIS TERHADAP STUDI DI INDONESIA - Hermanto, Hermanto; Ainnayah Poetri Zaika, Al; Ullifannuri, Ullifannuri; Prawibawa, Dian; Redjeki, Finny (Penerbit Lafadz Jaya, 2025)
Increasing competition in the industrial sector makes consumer loyalty an important focus in marketing strategies, including in the health sector. In health services such as in hospitals, patient loyalty is considered to be an indicator of success. Identifying the marketing mix that influences patient loyalty is a hospital strategy to maximize the quality of service to patients. This systematic review study aims to provide an overview of the influence of the marketing mix (7p) on patient loyalty in Indonesian hospitals. This study was conducted following the PRISMA guidelines. Literature research was conducted systematically through Scopus, PubMed, Epistemonikos, and Google Scholar databases. Of the 126 studies, 10 studies were included that assessed the influence of the marketing mix (7p) on patient loyalty. Each study was assessed for eligibility using the Newcastle-Ottawa Scale (NOS) adopted for cross-sectional. Of the 10 studies included, all were set in hospitals in Indonesia with publication years ranging from 2020-2025. This systematic review shows the influence of marketing mix on patient loyalty in hospitals through seven components, namely price, place, promotion, product, people, promotion, and physical evidence. The influential components of the marketing mix can vary between hospitals. Each element of the marketing mix has a different influence on patient loyalty in each hospital. Therefore, hospitals need to develop strategies to strengthen each element that is not yet optimal to increase patient loyalty.